Effects of Edaphic Fertilization and Foliar Application of Se and Zn Nanoparticles on Yield and Bioactive Compounds in Malus domestica L. - Anay Montaño-Herrera; Yair Olovaldo Santiago-Saenz; César Uriel López-Palestina; Gregorio Cadenas-Pliego; Zeus H. Pinedo-Guerrero; Alma Delia Hernández-Fuentes; José Manuel Pinedo-Espinoza (Horticulturae, 2022)
In this study, we evaluated the effects of edaphic fertilization with N, P, and K (150-50-80, 100-60-60, and without edaphic fertilization (SFE)) and foliar fertilization with nanoparticles (NPs) of Se and Zn (Se: 50 ppm, Zn: 250 ppm, and no nanoparticles (NP0)) on the yield and antioxidant compounds of apple fruits. We conducted this study in a 20-year-old commercial orchard. The experimental design was a randomized complete block design of nine treatments. The treatments with fertilization doses of 150-50-80 and 100-60-60, supplemented with Se and Zn NPs, generally increased the yield, sugar content, and ascorbic acid of the apple fruits. The SFE + NPZn treatment produced the highest increase (+193% compared with the control) in fruit yield. The SFE + NPSe and SFE + NPZn treatments led to higher contents of phenols and flavonoids, with maximum values of 7.6 mg GAE and 15.82 mg QE per gram of dry weight. These compounds presented a direct correlation with the antioxidant activity in the fruits. The foliar application of Se and Zn nanoparticles supplemented the soil fertilization with N, P, and K to improve the yield and bioactive-compound synthesis of the apple fruits.